Diseño de un modelo de incentivos no monetarios para la empresa FLEXIPLAST en el periodo noviembre 2014 – mayo 2015 - Aguirre Estrella, Julia Salomé (2017)
At FLEXIPLAST S.A., a company located in the Calderón area, the need for non monetary incentives has risen as a place where a co-worker should be more valuable than any monetary gain; this model should be highly cost efficient. Via survey, it was possible to attain an analysis of the work environment which, in turn, pointed at the need for a dynamic portfolio due to the constant change in the workplace and market, allowing for a more efficient adaptation of people to new organizational conditions. This responsibility falls upon the head of human resources whom will have the tools to recognize and reward abilities, promoting the worker’s loyalty through non monetary incentives and keeping a permanent support to this plan. Counting on an encouraged and motivated team is key to accomplishing the organizational objectives from committed individuals and teams, achieving a greater commitment to the company since it manages to make the collaborator feel valued as a professional and in the workplace. The challenge is to exploit the long term potential of human resources within the organization by means of a portfolio created for the company where its main axis is the acknowledgment of performance, fealty of the collaborator and his growth within the company.